Cross-Cultural Alliance-Making and Local Resistance in the Moluccas during the Revolt of Prince Nuku, c. 1780–1810 - Muridan S. Widjojo (Journal of Indonesian Social Sciences and Humanities, 2008)
Fine and rare spices were the primary reason for the Europeans to establish trading posts in Asia. The Dutch took control of the Moluccas at the beginning of the seventeenth century following the establishment of the Dutch East India Company (VOC) in 1602. The use of force and diplomacy to force out their trading rivalsthe Spaniards, Portuguese and their allieswas planned and designed from the outset. How the VOCs power structures were set up in the Spice Islands of eastern Indonesia differed from place to place. In Banda, the regions power structure and organisation of trade and politics was destroyed with the extermination and forced evacuation of the Bandanese population. In Ambon, the VOC established direct rule over an indigenous population that took sixty years to assure. In Ternate, the most important state in the Moluccas at that time, the VOC employed indirect rule; it ruled through the sultans, whom they kept on a short leash by controlling successions and putting their favourites on the throne.